2014
DOI: 10.1038/ni.2843
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomics analysis of signalosome dynamics in primary T cells identifies the surface receptor CD6 as a Lat adaptor–independent TCR signaling hub

Abstract: T cell antigen receptor (TCR)-mediated T cell activation requires the interaction of dozens of proteins. We used quantitative mass spectrometry and activated primary CD4 + T cells from mice in which a tag for affinity purification was knocked into several genes to determine the composition and dynamics of multiprotein complexes forming around the kinase Zap70 and the adaptors Lat and SLP-76. Most of the 112 high confidence time-resolved protein interactions we observed were novel. The CD6 surface receptor was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
140
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(154 citation statements)
references
References 53 publications
14
140
0
Order By: Relevance
“…In contrast, upon TCR stimulation, complex formation of ADAP and ZAP70 is not solely dependent on this single tyrosine because a larger TCR-associated complex is maintained in our experiment that contains both molecules (supplemental Fig. S5) (49). An indirect association of ADAP-Y571F with ZAP70 after TCR triggering is also supported by the finding that the other major tyrosine phosphorylation sites of ADAP are not recognized by ZAP70 in pull-down experiments (18,22,56).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In contrast, upon TCR stimulation, complex formation of ADAP and ZAP70 is not solely dependent on this single tyrosine because a larger TCR-associated complex is maintained in our experiment that contains both molecules (supplemental Fig. S5) (49). An indirect association of ADAP-Y571F with ZAP70 after TCR triggering is also supported by the finding that the other major tyrosine phosphorylation sites of ADAP are not recognized by ZAP70 in pull-down experiments (18,22,56).…”
Section: Discussionsupporting
confidence: 63%
“…Using either Flag-tagged wild type or Y571F mutant of ADAP the presence of ZAP70, LAT, PLC␥1, and SLP76 was verified as previously described for the ZAP70, LAT or SLP76 interactome (supplemental Fig. S5) (49). In contrast to TCR stimulation it was previously shown that this supramolecular assembly is not formed upon chemokine stimulation (39).…”
Section: The Adap and Zap70 Interaction Is Inducible In A Cellularmentioning
confidence: 99%
“…Using homologous recombination in Escherichia coli (30), a chloramphenicolresistance gene bracketed by BspEI and SalI sites was inserted at the 39 end of the Pag1-coding sequence found in exon 9. The chloramphenicolresistance gene was excised using BspEI and SalI digestion and replaced by a XmaI-SalI fragment corresponding to a one-STrEP tag (OST)-(Stop) 2loxP-tACE-CRE-PGK-gb2-neo-loxP cassette (29). Finally, the targeting construct was abutted to a thymidine kinase expression cassette and linearized with FseI.…”
Section: Pag1mentioning
confidence: 99%
“…Affinity purification coupled with mass spectrometry (AP-MS) allows highly sensitive analysis of the dynamics of noncovalent protein complexes. We developed mice that bear a genetic tag that permits AP-MS analysis of protein complexes isolated from primary CD4 + T cells at different time points following T cell activation (29). Considering that this approach provided a systems-level understanding of the TCR signal-transduction network and identified proteins that have not been observed in the context of TCR signaling, to our knowledge, we used it in the current study to decipher the dynamics of the PAG signalosome in thymocytes and CD4 + T cells.…”
Section: T He Recognition Of Peptide-mhc (Pmhc) Ligands By T Cells Anmentioning
confidence: 99%
See 1 more Smart Citation